A novel incremental slide board test for speed skaters: Reliability analysis and comparison with a cycling test - Piucco, T.; dos Santos, S. G.; Dantas de Lucas, R.; Ache Dias, J. (Apunts Medicina de l'Esport, 2015)
Exercise prescription from indices obtained from cycling or running treadmill incremental tests does not seem suitable for speed skaters. However, the specificity of laboratory skating assessments remains to be established. Purpose